POTENCY OF SOIL WATER IN MASINAM ISLAND BASED ON THE ROCK RESISTIVITY VALUE - Firmansyah, Yusi; Restu, Abigail; Suganda, Bombom Rachmat; Dwi Hadian, Mohammad Sapari; Ganjar Gani, Reza Mohammad (Journal of Geological Sciences and Applied Geology, 2018)
Groundwater is water that is contained in soil layers or rocks that are located below the soilsurface. The resistivity or geoelectric method is used to obtain an anomaly of material under thesurface using electrical properties. 2 Dimensional Geoelectric Measurements are carried out asmany as 5 Tracks. From the results of the analysis based on surface data, the resistivitydistribution value in the study area can be interpreted to obtain 3 rock packages with low, mediumand high types of resistance. If it has low resistance (smaller than 45 Ωm), the lithology in thispackage is claystone, this layer is interpreted as not being able to store water and tends to easilyescape the water. While the value of the medium type of resistance (45 μm to 200 Ωm) has goodporosity. The lithology of this package is interpreted as sandstone. Lithology at high resistivityvalues (greater than 200 Ωm), is interpreted as limestone. This limestone layer is presumed tohave undergone a karstification process and presumably, this layer has the potential to be a goodaquifer that can accommodate enough water and drain at a certain time.